Are There Gender Differences in Politeness? A Sociopragmatic Analysis of Guests’ Opinions in Podcast - Aninda Ayu Sitorismi; Arief Ma'nawi (Universitas Ahmad Dahlan, 2026)
Studies on language and gender describe females as more polite, indirect, and cooperative, while males are portrayed as more assertive. However, these generalizations do not fully reflect the complexity of language use in the Arab digital context, as Arabic language use remains deeply embedded in gender-based social structures, including politeness. Podcasts, as an emerging digital medium, offer a more open space where guests may negotiate or even shift these expectations. This study raises an important question: do gendered politeness patterns in podcasts indicate a shift from traditional stereotypes, or continue to reflect established norms? This study examines two Finjān podcast episodes by (1) identifying the politeness strategies employed by male and female guests when expressing opinions and (2) examining the patterns and trends in its use. Employing a descriptive qualitative approach, the data were collected through Simak method and analyzed using Brown and Levinson’s (1987) framework. Findings reveal that both guests employed all four strategies: bald on record, positive politeness, negative politeness, and off record, but with varying frequencies. Positive politeness was the most used by guests, reflecting the importance of solidarity and interpersonal closeness in discussions on parenting. The female guest consistently employed a combination of positive and negative politeness to maintain conversational harmony, while male guests, in addition to positive politeness, also employed off record strategies, including metaphors and illustrative examples, to reduce face threats. These tendencies suggest a subtle reshaping of gendered norms in digital interaction, while still reflecting broader social expectations.